Sarcoid-like foreign body reaction in body piercing - a report of two cases - Han, K.; Siar, C.H.; Ganesapillai, T.; Lumpur, K. (1997)
We report two cases of body piercing as a religious practice that subsequently led to the development of granulomatous nodules at previously punctured sites of the skin and oral mucosa. These lesions were diagnosed as sarcoid-like foreign body reaction after other possible causes including sarcoidosis, tuberculosis, tuberculoid leprosy, fungal infections, viral infections, and Crohn's disease were excluded.